Genetic and biochemical studies of transport systems for branched-chain amino acids in Escherichia coli K-12: isolation and properties of mutants defective in leucine-repressible transport activities. - Yamato, I (1980)
The characteristics of a mutant (hrbA) of Escherichia coli K-12 that is defective in a leucine-nonrepressible transport system, the LIV-3 system, for branched-chain amino acids were described previously (I. Yamato et al., J. Bacteriol 138:24-32, 1979). New mutants requiring a high concentration of isoleucine for growth were isolated from strain B763 (hrbA ileA) after mutagenesis with ethyl methane sulfonate. These mutants had a defect of the leucine-repressible transport activities for branched-chain amino acids of the parental strain. One of these mutants, strain B7634, had defects of two independent genetic loci (hrbBC and hrbD). The genes hrbBC were mapped at min 76 near malT, and the gene hrbD mapped at min 77 near xyl on the E. coli genetic map. The substrate specificity, kinetic properties, and source of coupling energy of the transport system coded for by each of these genes were studied using cytoplasmic membrane vesicles and intact cells. The results identified three transport systems with characteristic features other than the LIV-3 system. The hrbB and hrbC systems are responsible for the uptake activites of the LIV-2 system, with a high Km value, and the LIV-1 system, with a low Km value, respectively. Both activities are repressed by leucine and inhibited by threonine and the b(--) isomer of 2-aminobicycloheptyl-2-carboxylic acid. They both utilize adenosine 5'-triphosphate as coupling energy and are not detected in cytoplasmic membrane vesicles. The hrbD system is responsible for the LIV-4 system, with a high Km value. Its activity is repressed by leucine and partially inhibited by threonine. It is detected in cytoplasmic membrane vesicles with a proton motive force as the driving energy.